2018
DOI: 10.1016/j.humimm.2018.04.012
|View full text |Cite
|
Sign up to set email alerts
|

HLA -A, -C, -B, -DRB1, -DQB1 and -DPB1 allele and haplotype frequencies in 4514 healthy Norwegians

Abstract: We report HLA-A, -C, -B, -DRB1, -DQB1 and -DPB1 allele frequencies and estimated haplotype frequencies from 4514 healthy Norwegians who volunteered to participate in the Norwegian Bone Marrow Donor Registry. HLA genotyping was conducted on a Next Generation Sequencing platform. Data were analyzed using Arlequin and Pypop software. No significant deviations from Hardy-Weinberg Equilibrium were noted at any of the loci studied. We discuss the representability for the Norwegian population and argue that the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 157 publications
0
17
1
Order By: Relevance
“…Wennerstr€ om et al [48] reported extended DRB1 (HLA class II) haplotypes from a Finnish population sample of 150 individuals in 2013. More recently, Norwegian and Russian Karelian 6-locus haplotype frequencies were reported [47,49]. To our knowledge, no studies on the strength of the linkage disequilibrium between 5-locus HLA haplotypes and DPB1 have been published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wennerstr€ om et al [48] reported extended DRB1 (HLA class II) haplotypes from a Finnish population sample of 150 individuals in 2013. More recently, Norwegian and Russian Karelian 6-locus haplotype frequencies were reported [47,49]. To our knowledge, no studies on the strength of the linkage disequilibrium between 5-locus HLA haplotypes and DPB1 have been published.…”
Section: Discussionmentioning
confidence: 99%
“…In connection with AH 8.1, the frequency of DPB1*01:01 was .26 in the United Kingdom and .34 in Germany, whereas the average DPB1*01:01 frequencies in these populations were .08 and .04 to .05 respectively [46]. Similarly, for AH 35.2 the frequency of DPB1*04:02 was greater than .4 in Germany, Britain, Poland, and Sweden, the frequency thus being 4-to 10-fold compared with the average frequency of DPB1*04:02 in these countries [46], and DPB1*05:01 was 5to 6-fold over-represented in connection with AH 7.1 in the United Kingdom, Germany, and Norway [47]. The results indicate that all DPB1 associations described in this study are not unique to Finland.…”
Section: Dpb1 Associations In Other Populationsmentioning
confidence: 99%
“…The median sequencing depth was above 150 reads per called base. The 4511 healthy Norwegian controls had previously been HLA typed by NGS 52 . Both patient and control genotypes were analyzed at 2nd field resolution for HLA -A, -B, -C, -DRB1, -DQB1 and -DPB1.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of different HLA‐DR‐DQ haplotypes in the Norwegian population is known from typing by the Norwegian Bone Marrow Registry 15,17,19 . We have focused on the most common haplotypes.…”
Section: Discussionmentioning
confidence: 99%